Pressure broadening and narrowing due to oxygen and nitrogen gas mixtures at 1270 nm band: part III - Ahmad Al-Jalali , Muhammad (International Journal of Physical Research, 2024)
Collisional effects on the absorption spectrum of oxygen and nitrogen gas mixtures at 1270 nm band appear as a broadening or narrowing at the component of Lorentzian width in the Voigt profile. The deconvolution method of spectral lines reveals two kinds of bands, the first centered at 1264 nm, and the second centered at 1268 nm. At high pressures, the Gaussian full width may be fixed, and Voigt's full width at half maximum (FWHM) nearly equals to Lorentzian full width. Partial pressures of each gas were between 1-10 bar at 298 K. New results highlight the effect of nitrogen as a collisional partner on the oxygen spectrum. PACS: 32.30. Bv; 33.20. Ea; 33.20.-t; 34.50.-s; 34.50. Ez; 51.30. +I; 87.64. km.